Fistula after primary palatoplasty: consensus among plastic surgery and Speech-Language Pathology - Mahyara Francini Jacob; Gabriela Aparecida Prearo; Telma Vidotto de Sousa Brosco; Hagner Lucio de Andrade Silva; Jeniffer de Cassia Rillo Dutka (Revista Brasileira de Cirurgia Plástica)
Introduction: The identification of complications of primary palatoplasty may vary among professionals from different areas of health due to the lack of standardization of the fistula classification. This study aimed to verify the consensus among professionals of plastic surgery (PC) and Speech-Language Pathology (SLP), regarding the occurrence of fistula, according to what was reported in the same craniofacial service. Methods: Analysis of the chart's records of the areas of the PC and SLP of 466 patients with cleft lip and palate was performed about the presence and location of fistula about the presence and location of fistulas, as reported in 466 medical records of patients with a history of unilateral cleft lip and palate. To compare the findings between both areas, a gold standard classification for the occurrence of fistula (GSF) was established by an experienced plastic surgeon. Results: The PC area reported that 25% of the 466 patients had a fistula compared to the 37% reported by the SLP, while the GSF indicated fistula in 35% of the cases. The Kappa statistic reveals regular agreement between GSF and PC (r = 0.32) and substantial agreement between GSF and SLP (r = 0.63). Conclusion: There was a discrepancy between the areas of Speech-Language Pathology and plastic surgery regarding the occurrence and location of the fistula after primary palatoplasty in the same craniofacial center. The data indicates the need to create and implement a standardized fistula classification system. In this way, craniofacial teams can use it effectively, taking advantage of the scientific evidence that emerges from the results of cleft lip and palate treatment.